Procedure of bedsore prophylactic as a tool of nurse care quality assessment - Kiełbasa, Lucyna (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2010)
Introduction : Bedsore is a type of chronic wound and concerns long term immobilized patients with serious health ailment. Implementation, into nurse practice, standardized procedure of bedsore prophylactic affects favorable quality, effects for both, patients and hospital. Aim : The main goal of this research is assessment of influence of application of bedsore prophylactic on level of nurse care effectiveness, expressed in bedsore prophylactic indicator. Material and methods: The Doren Norton scale was used to assess the risk of bedsore. Documentation of bedsore prophylactic team and individual patients documentation of 10 762 patients hospitalized in years 2004-2009 were analyzed. Results : During the six years encompassing researching period of time, the number of 10 762 patients with the risk of bedsore was separated. That makes up 13.75% all patients hospitalized in hospital. From this group of patients there ware 10 014 patients who ware preserwed from bedsore. This wllowed to achieve the bedsore prophylactic indicator on the level 93.04%. Conclusions : It has been established, that implementation of procedure allows to separate group of patients with the risk of bedsore, and putting the pattern into practise allows to preserve a big group of them from bedsore. High level of prophylactic indicator points at high level of nurse care.